Analysis of Tahubudi product strategy in facing competition using Porter's five forces and Islamic perspective - Winata, Reihan Arya; Syafina, Laylan; Harahap, Muhammad Ikhsan (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2024)
This research aims to investigate and analyze the tofu product strategy employed by Budi in response to business competition. The study was conducted at Tahu Budi Household Industry, an MSME located in Deli Serdang Regency. A qualitative approach was employed to gather and analyze the data, primarily consisting of Budi's competitive strategy, obtained through interviews with the business owners. Data collection techniques involved observation, interviews, and documentation. Porter's Five Forces of Competition Theory was utilized as the analytical tool for assessing the competitive strategy. The findings indicate that Tahu Budi can compete with its rivals regarding price, product quality, promotion, and distribution. In order to sustain their operations, they need to streamline production costs and enhance their marketing integration, as adaptable businesses thrive amidst environmental changes. Public interest statements This research is highly relevant for micro, small, and medium enterprises (MSMEs) in any industry, particularly the home industry of tofu production, as it explores effective competitive strategies that can contribute to their sustainability.